2001
DOI: 10.1177/104063870101300303
|View full text |Cite
|
Sign up to set email alerts
|

PCR-Based Detection of an Emerging Avian Pneumovirus in US Turkey Flocks

Abstract: Abstract. Avian pneumovirus (APV) or turkey rhinotracheitis virus (TRTV) is an important respiratory pathogen of domesticated poultry in many countries in Europe, Africa, and Asia. Until recently, the United States was considered free of APV. In late 1996, an atypical upper respiratory tract infection appeared in turkey flocks in Colorado and shortly thereafter in turkey flocks in Minnesota. An avian pneumovirus (APV-US) that was serologically distinct from the previously described TRTV was isolated as the pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
31
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 17 publications
1
31
0
1
Order By: Relevance
“…A few flocks from the neighbourin g states of North and South Dakota have also been found to be serologically positive for APV infection (Lauer, 2000). A similar disease is present in European turkeys, but the US isolates of APV have been shown to differ antigenically and genetically from the A and B subtypes of European APV (Seal, 1998;Panigrahy et al, 2000;Seal et al, 2000;Dar et al, 2001). Recently, a subgroup D strain of APV has been reported (Bäyon-Auboyer et al, 2000).…”
Section: Introductionmentioning
confidence: 94%
“…A few flocks from the neighbourin g states of North and South Dakota have also been found to be serologically positive for APV infection (Lauer, 2000). A similar disease is present in European turkeys, but the US isolates of APV have been shown to differ antigenically and genetically from the A and B subtypes of European APV (Seal, 1998;Panigrahy et al, 2000;Seal et al, 2000;Dar et al, 2001). Recently, a subgroup D strain of APV has been reported (Bäyon-Auboyer et al, 2000).…”
Section: Introductionmentioning
confidence: 94%
“…The virus causes upper respiratory tract infection in turkeys and chickens of all ages and is prevalent worldwide as indicated by serological testing (Jones, 1996). Existing APV strains have been classified into four subgroups, namely subgroups A, B, C, and D. Subgroup C is prevalent in the US (Seal, 1998;Seal et al ., 2000;Dar et al ., 2001) while subgroups A, B, and D are found mainly in Europe (Cook & Cavanagh, 2002). The subgroup C of APV was isolated initially by inoculation of samples in chicken embryo fibroblast cultures followed by adaptation of the virus isolate in Vero cells (Goyal et al ., 2000).…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that NP-40 extraction may enrich the external viral proteins, whereas freeze/thaw treatment may enrich internal components of the virus. Discrepancies in TRTV ELISA results with different antigens have been reported 6 and it has been suggested that the efficiency of serological testing may improve if the test uses antigens prepared from virus strains originating from different geographical areas.…”
mentioning
confidence: 99%
“…17 Although the Colorado and Minnesota isolates of APV are similar to TRTV antigenically, major differences have been found among them. 6 This study reports on the detection of antibodies to APV infection in Minnesota turkeys.…”
mentioning
confidence: 99%
See 1 more Smart Citation